Биотехническая система оценки слизистой оболочки верхних дыхательных путей - Носова, Я. В.; Аврунин, О. Г.; Калашник, Ю. М.; Шушляпина, Н. А. (НТУ "ХПИ", 2014)
В статье обосновывается необходимость разработки новых неинвазивных методов диагностики оториноларингологических заболеваний, предлагается структурная схема биотехнической системы оценки слизистой оболочки верхних дыхательных путей человека, а также информационная модель процесса обработки изображения слизистой оболочки полости носа, обоснован выбор информативных показателей эндоскопического снимка слизистой оболочки носовой полости. Определены наиболее значимые диагностические параметры эндоскопического изображения.

The necessity of the development of new non-invasive diagnostic methods otorhinolaryngological diseases, proposed a block diagram of the biotechnical system evaluation mucosa of the upper respiratory tract, as well as the information model of the processing of the image of the nasal mucosa, justified the choice of informative indicators endoscopic image of the mucous membrane of the nasal cavity. The prospect of work is to conduct further analysis in order to identify correlations among the diagnosis as well as informative parameters investigated endoscopic image to enhance the effectiveness of early diagnosis and reduce the time of diagnosis, which will significantly reduce the time of treatment. Further increase the accuracy of assessment of mucosal possible by maximizing the identical conditions of the study. Determined the most important diagnostic parameters endoscopic images.
Biotechnical assessment system mucosal upper respiratory tract
Keywords: гиперемия; модель цветовая; носовая полость; эндоскоп; hyperemia; color model; nasal airways; image; endoscope